2000
DOI: 10.1111/j.8755-8920.2000.440606.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Epididymis‐Specific Antigens Using Neonatal Tolerization

Abstract: The results of this study demonstrate that neonatal tolerization with testicular sperm proteins, followed by immunization with epididymal sperm proteins, enhances the production of antibodies to proteins exclusively of epididymal origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…Klinefelter & Hamilton (1985) have shown that mammalian sperm on leaving the testis acquire fertilizing ability after interacting with epididymal secretory products especially in the caput region. Report from our earlier study has also indicated that the 29 kDa protein appeared from distal caput and increased in the corpus region (Khole et al 2000). Our present data also indicate similar pattern of reactivity.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Klinefelter & Hamilton (1985) have shown that mammalian sperm on leaving the testis acquire fertilizing ability after interacting with epididymal secretory products especially in the caput region. Report from our earlier study has also indicated that the 29 kDa protein appeared from distal caput and increased in the corpus region (Khole et al 2000). Our present data also indicate similar pattern of reactivity.…”
Section: Discussionsupporting
confidence: 90%
“…The approach used in the present study was modified to overcome the lack of high throughput capacity of the earlier approach. The approach differs in terms of several aspects from the studies reported earlier (Ensrud & Hamilton 1991, Khole et al 2000. First, in this study, we used extracts from different sperm domains, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations